Beberapa Faktor Risiko Gizi Kurang dan Gizi Buruk pada Balita 12-59 Bulan (Studi Kasus di Kota Pontianak) - Dedi Alamsyah; Maria Mexitalia; Ani Margawati; Suharyo Hadisaputro; Henry Setyawan (Jurnal Epidemiologi Kesehatan Komunitas, 2017)
Background: Moderate and severe malnutrition cases in Pontianak City increases each year although a nutritional improvement program has been held by the Health Department of Pontianak City.Method: The type of research was observational using the quantitative study design of case control study and the qualitative study through in-depth interview (mixed method). The number of samples was 80 people consisting of 40 people from case and 40 people from control. Assessment of nutritional using anthropometry measurement based on weight for height. Height measurement using microtoise and measure weighting scale.Results: The multivariate analysis found 2 variables signiﬁcantly associated with the prevalence of moderate and severe malnutrition in children under ﬁve years old aged 12-59 months, i.e.: poor of attitude toward food (OR = 6.980) and poor environmental health (OR =5.033). There were 9 variables which were not associated with nutritional status, not given exclusive breastfeeding, energy intake is less, protein intake is less, frequency of Severe Acute Respiratory Infection equal to over three times in the last two months, frequency of diarrhea equal to over three times in the last two months, low monthly family income, number of children more than two, low mother's education, and frequency of watching TV more than two hours a day.Conclusion: Based on the results above, it can be concluded that the risk factors associated with the prevalence of moderate and severe malnutrition are poor of mother's attitude toward food is poor health and poor environmental.